Relations Among Gender, Violence Exposure, and Mental Health: The National Survey of Adolescents - Amstadter, Ananda (2008)
Using a nationally representative sample of 4,008 adolescents, this study examines gender differences in violence exposure, major depressive episode (MDE) and posttraumatic stress disorder (PTSD), and characteristics of violence incidents. It was hypothesized that there would be gender differences in the types of violence exposure reported as well as the prevalence of MDE and PTSD; and that gender would moderate the relationship between violence exposure and mental health outcomes. Results indicated significant gender differences in rates of violence exposure, PTSD and MDE. Additionally, gender was a moderating variable in the relation between sexual assault and PTSD, but not in the other violence exposure-mental health relations examined. It thus appears that the pathways for developing PTSD may be different for male and female victims of sexual abuse. Implications for interventions and future research are discussed